Mechanical Changes and Microfilament Reorganization Involved in Microcystin-LR-Promoted Cell Invasion in DU145 and WPMY Cells - Zhang, Qiang; Wang, Guihua; Xie, Yongfang; Gao, Zhiqin; Liang, Zumu; Pan, Zhifang; Wang, Guohui; Feng, Weiguo (Frontiers in Pharmacology, 2020)
Microcystin-leucine arginine (MC-LR) is a potent tumor initiator, which could induce cell malignant transformation. Cellular mechanical characteristics are pivotal parameters which are closely related to cell invasion. The aim of this study is to determine the effect of MC-LR on mechanical parameters, microfilament and cell invasion in DU145 cells and WPMY cells. Firstly, 10 μM MC-LR was selected as the appropriate concentration by the relative cell viability testing. Subsequently, after MC-LR treatment, the cellular deformability and viscoelastic parameters were tested using micropipette aspiration technique. The results showed that MC-LR increased the cellular deformability, reduced the cellular viscoelastic parameters and caused the cells became softer. Furthermore, microfilament and microfilament-associated proteins were examined by immunofluorescence and western blot, respectively. The results showed that MC-LR induced microfilament reorganization and increased the expression of p-VASP and p-ezrin. Finally, the impact of MC-LR on cell invasion was evaluated. The results revealed that MC-LR promoted cell invasion. Taken together, our data suggested that mechanical changes and microfilament reorganization involved in MC-LR-promoted cell invasion in DU145 cells and WPMY cells. Our results provided novel information to explain the toxicological mechanism of MC-LR.